Digital literacy competency of elementary school teachers: A systematic literature review - Hamidulloh Ibda; Ibnu Syamsi; Rukiyati Rukiyati (Institute of Advanced Engineering and Science, 2023)
The article presents a literature review on the digital literacy competencies of elementary school teachers. The method used is a systematic literature review with the process of determining objectives, searching for literature, selecting articles by reading abstracts and keywords, reading articles as a whole, abstracting data, and presenting the results of analysis of recent articles using the publish or perish 7, Mendeley, VOSviewer, and NVIVO 12 Plus applications. The search for articles in Scopus-indexed journals is limited to 2018-2022. From searching articles through publish or perish 7, there were 259 pieces. Then 259 articles were selected into 50 articles according to relevance to research questions. The results of the topic findings in the 50 articles through the help of the VOSviewer are the use of devices in learning, use of digital media in learning, the impact of digital literacy in learning, digital literacy, digital competence, digital literacy ability, digital collaboration, digital technology, literacy, technology, computer literacy, and others. The selected articles were analyzed according to the research questions through the NVIVO 12 plus and described in narrative form. This article contributed to future research and became a study for the theme of digital literacy competence.